Pengujian Orifice Flow Meter dengan Kapasitas Aliran Rendah - Ainul Ghurri; S.P.G. Gunawan Tisna; Syamsudin Syamsudin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2016)
Orifice flow meter is used in many laboratory and industrial application due because of its simple design and low cost. The present research investigated an orifice flow meter operated in relatively low flow rate. Orifice plate is a metal plate, 10 mm width provided with bevel at inlet section. The diameter ratios (β) are 0.3, 0.4, 0.5, 0.6, 0.7, and 0.8, respectively. The experiment used water with flowrate range having Reynolds number between 6827,55 and 8004,72. The fluid is flown through the orifice plate. Pressure taps are used to measure pressure at upstream and downstream of the orifice plate. The actual capacity is directly measured at an outlet reservoir; while the theoretical capacity is calculated using modified Bernoulli equation with diameter ratio (β) within the equation. The results showed that the irrecoverable pressure drop decreased with the increase of flow capacity and the diameter ratio. The discharge coefficient of the orifice flowmeter ranged between 0.3 and 1.3.